2021
DOI: 10.4317/medoral.24318
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter observational study on Medication-Related Osteonecrosis of the Jaw (MRONJ) in advanced cancer and myeloma patients of a cancer network in North-Western Italy

Abstract: Background Incidence of Medication-Related Osteonecrosis of the Jaw (MRONJ) related to cancer and myeloma treatments is undetermined, with scarce data varying from 2 to 7.8/million/year in limited investigated populations. A 9-years [2009-2018] regional-wide survey was conducted, deploying the North-Western Italy Cancer Network (“Rete Oncologica Piemonte e Valle d’Aosta”), to assess number and main characteristics of MRONJ cases among myeloma/cancer patients, within a population of 4.5 million inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In the case of systemic diseases, excluding those involving the use of these drugs, cardiovascular diseases and rheumatoid arthritis are highlighted [ 77 , 78 , 79 ]. Among the medical factors: chemotherapy, corticosteroids, smoking vitamin D deficiency, renal dialysis, anemia, Paget’s disease of bone, erythropoietin therapy, cyclophosphamide therapy, alcohol intake, and obesity are the most frequently reported [ 80 , 81 , 82 ]. Due to the scarce number of longitudinal studies involving this outcome, results make it difficult to quantitatively assess the thresholds for the level of damage of each of them individually [ 83 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…In the case of systemic diseases, excluding those involving the use of these drugs, cardiovascular diseases and rheumatoid arthritis are highlighted [ 77 , 78 , 79 ]. Among the medical factors: chemotherapy, corticosteroids, smoking vitamin D deficiency, renal dialysis, anemia, Paget’s disease of bone, erythropoietin therapy, cyclophosphamide therapy, alcohol intake, and obesity are the most frequently reported [ 80 , 81 , 82 ]. Due to the scarce number of longitudinal studies involving this outcome, results make it difficult to quantitatively assess the thresholds for the level of damage of each of them individually [ 83 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Recent data suggest that combination therapies might also increase the risk of developing MRONJ and cause more advanced necrosis especially in the maxilla; however, this study was not limited to patients with myeloma [22]. Another study of 459 MRONJ cases reported that out of 52 patients undergoing treatment with BMA, 11 had also received lenalidomide, 12 received thalidomide, 11 received bevacizumab, 9 received everolimus, and 9 received sunitinib as part of the drug therapy [2]. Although bisphosphonates are the drugs most frequently associated with MRONJ, there is a growing range of non-antiresorptive medications implicated in MRONJ development [23].…”
Section: Medicationsmentioning
confidence: 99%
“…It can cause serious functional disturbance, morbidity, and adversely impact quality of life [1]. Although uncommon, MRONJ is in fact not a rare adverse event in myeloma patients; therefore, continuous monitoring and vigilance is essential from haemato-oncologists, and dental and oral maxillofacial specialists [2].…”
Section: Introductionmentioning
confidence: 99%
“…From the 25 studies that were included for full-text analysis, 14 were excluded; six studies only reported a single arm MRONJ case series or a case control study from which prevalence could not be assessed, [32][33][34][35][36][37] seven studies did not include/specify any AA therapy, [38][39][40][41][42][43][44] and one record was a conference abstract for which a full text was included from the original search. [45] Finally, a total of 11 full texts with extractable data were included in the qualitative and quantitative syntheses.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%